ANALYSIS OF THE SUCCESS OF BUSINESS MODELS OF UKRAINIAN COMPANIES ON THE EUROPEAN MARKET USING THE EXAMPLE OF INTERNATIONAL COMPANIES - Ю. О. Гавриш; О. В. Зозульов; А. Л. Симоненко (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The article examines aspects of the success of business models of Ukrainian enterprises on the European market. Through the prism of the analysis of successful exits and failures of Ukrainian companies, such as Grammarly, AgroPharm, Aurora, etc., the key factors that determine competitiveness at the international level are highlighted. The purpose of the article was to consider approaches to the definition of the concept of "business model" and to analyse the success of business models of Ukrainian enterprises in the European market through the prism of this. The economic, technological and international aspects of the success of business models of enterprises are considered. The analysis of cases of Ukrainian enterprises entering the European market allowed us to identify the key success factors during such an exit, revealing the importance of product quality, strategic marketing, social responsibility and flexibility in interaction with different cultural and economic conditions. The general conclusion emphasizes the need for a comprehensive approach to entering the European market and constant improvement of strategies to ensure sustainable success in the global business environment.